2015
DOI: 10.4317/medoral.20410
|View full text |Cite
|
Sign up to set email alerts
|

Alpha lipoic acid efficacy in burning mouth syndrome. A controlled clinical trial

Abstract: BackgroundA double-blind placebo-controlled trial was conducted in order to evaluate the efficacy of alpha lipoic acid (ALA) and determine the statistical significance of the outcome variables. Burning mouth syndrome (BMS) is defined as an oral burning sensation in the absence of clinical signs which could justify the syndrome. Recent studies suggest the existence of neurological factors as a possible cause of the disease.Material and Methods60 patients with BMS, in two groups: case group with 600 mg/day and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 23 publications
(25 reference statements)
0
92
0
1
Order By: Relevance
“…12) Results pertaining to the therapeutic effect of alpha-lipoic acid are mixed and inconclusive. Some studies 13,14) reported improvement, while others [15][16][17] failed to demonstrate effectiveness over placebo.…”
Section: Discussionmentioning
confidence: 99%
“…12) Results pertaining to the therapeutic effect of alpha-lipoic acid are mixed and inconclusive. Some studies 13,14) reported improvement, while others [15][16][17] failed to demonstrate effectiveness over placebo.…”
Section: Discussionmentioning
confidence: 99%
“…A final recent RCT found in favour of α‐LA 600 mg/day for 2 months over placebo (16/25 patients improving in the active arm versus 8/29 in the placebo group, P < 0.05) . There were significant methodological and reporting deficiencies in the study.…”
Section: Treatmentmentioning
confidence: 97%
“…Idiopathic BMS represents chronic intraoral burning sensation for which no local or systemic cause can be found, and clinical examination shows no pathological changes in oral mucosa . It has been shown that many disorders such as Xerostomia, oral infections, denture‐related problems, allergies, diseases of oral mucosa, Sjogren's syndrome, nutritional deficiencies, hormonal disturbances, some endocrine disorders, oesophageal reflux, medication side effects, depression, anxiety, hypochondriasis and cancerophobia are associated with BMS, although a causative relationship has not been proven between BMS and a majority of these disorders …”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of BMS are usually bilateral. They do not follow the anatomical distribution of peripheral sensory nerve, and their intensity varies during the day and rarely affects sleep . They include burning sensation which most commonly affects the tongue, then lips, palate and gingival, or a whole oral cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation